Risk of increased acceptance for organizational nepotism and cronyism during the COVID-19 pandemic - Grzegorz Ignatowski; Łukasz Sułkowski; Bartłomiej Stopczyński (Risks, 2021)
Nepotism and cronyism are forms of favoritism towards certain people in the workplace. For this reason, they constitute a problem for organization managers, ethicists and psychologists. Identifying the impact of COVID-19 pandemic on the increase of nepotism and cronyism may provide a basis for organizations to assess their extent and to take possible measures to prevent their negative effects. At the same time, the research presented in the article may provide a basis for further research work related to nepotism and cronyism at the times of other threats, different from the pandemic. The aim of the article is to examine the impact of the COVID-19 pandemic on growing acceptance for nepotism and cronyism in Polish enterprises. Qualitative and quantitative methods have been included in the conducted research. Qualitative study aimed at improving knowledge of nepotism and cronyism and the impact of the COVID-19 pandemic on these phenomena, followed by a quantitative study conducted in order to verify the information obtained in the qualitative study. This research has demonstrated that Nepotism and cronyism in the workplace, are phenomenon that are basically evaluated negatively. They adversely influences social and economic development, but the impact of COVID-19 pandemic on nepotism and cronyism is not significant.
Keywords: 330; COVID-19; cronyism; nepotism; nepotism acceptance; pandemic